Male‐biased dispersal in a fungus‐gardening ant symbiosis - Alix E. Matthews; Katrin Kellner; Jon N. Seal (Ecology and Evolution, 2021)
Abstract For nearly all organisms, dispersal is a fundamental life‐history trait that can shape their ecology and evolution. Variation in dispersal capabilities within a species exists and can influence population genetic structure and ecological interactions. In fungus‐gardening (attine) ants, co‐dispersal of ants and mutualistic fungi is crucial to the success of this obligate symbiosis. Female‐biased dispersal (and gene flow) may be favored in attines because virgin queens carry the responsibility of dispersing the fungi, but a paucity of research has made this conclusion difficult. Here, we investigate dispersal of the fungus‐gardening ant Trachymyrmex septentrionalis using a combination of maternally (mitochondrial DNA) and biparentally inherited (microsatellites) markers. We found three distinct, spatially isolated mitochondrial DNA haplotypes; two were found in the Florida panhandle and the other in the Florida peninsula. In contrast, biparental markers illustrated significant gene flow across this region and minimal spatial structure. The differential patterns uncovered from mitochondrial DNA and microsatellite markers suggest that most long‐distance ant dispersal is male‐biased and that females (and concomitantly the fungus) have more limited dispersal capabilities. Consequently, the limited female dispersal is likely an important bottleneck for the fungal symbiont. This bottleneck could slow fungal genetic diversification, which has significant implications for both ant hosts and fungal symbionts regarding population genetics, species distributions, adaptive responses to environmental change, and coevolutionary patterns.